Intrahousehold power inequalities and cooperation: Unpacking household responses to nutrition‐sensitive agriculture interventions in rural India - Helen Harris‐Fry; Audrey Prost; Emma Beaumont; Emily Fivian; Satyanarayan Mohanty; Manoj Parida; Ronali Pradhan; Satyapriya Sahu; Shibanath Padhan; Naba K. Mishra; Shibanand Rath; Suchitra Rath; et al. (Wiley, 2023)
Abstract Nutrition‐sensitive agriculture (NSA) interventions offer a means to improve the dietary quality of rural, undernourished populations. Their effectiveness could be further increased by understanding how household dynamics enable or inhibit the uptake of NSA behaviours. We used a convergent parallel mixed‐methods design to describe the links between household dynamics-specifically intrahousehold power inequalities and intrahousehold cooperation-and dietary quality and to explore whether household dynamics mediated or modified the effects of NSA interventions tested in a cluster‐randomized trial, Upscaling Participatory Action and Videos for Agriculture and Nutrition (UPAVAN). We use quantitative data from cross‐sectional surveys in 148 village clusters at UPAVAN's baseline and 32 months afterwards (endline), and qualitative data from family case studies and focus group discussions with intervention participants and facilitators. We found that households cooperated to grow and buy nutritious foods, and gendered power inequalities were associated with women's dietary quality, but cooperation and women's use of power was inhibited by several interlinked factors. UPAVAN interventions were more successful in more supportive, cooperative households, and in some cases, the interventions increased women's decision‐making power. However, women's decisions to enter into negotiations with family members depended on whether women deemed the practices promoted by UPAVAN interventions to be feasible, as well as women's confidence and previous cultivation success. We conclude that interventions may be more effective if they can elicit cooperation from the whole household. This will require a move towards more family‐centric intervention models that empower women while involving other family members and accounting for the varied ways that families cooperate and negotiate.